2017
DOI: 10.1016/j.freeradbiomed.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and vasorelaxant effect of Diapocynin in normotensive rats

Abstract: Nicotinamide adenine dinucleotide phosphate oxidase (NAD(P)H-oxidase) is a multicomponent enzyme system that generates superoxide anion by one-electron reduction of molecular oxygen and represents the major source of reactive oxygen species (ROS) in the vascular cells. Apocynin has been extensively used as an inhibitor of NADPH oxidase (NOX) in phagocytic cells and as an antioxidant in non-phagocytic cells. In phagocytes cells, due to the presence of myeloperoxidase, apocynin can be the converted to diapocynin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…The same author further justifies the increased inhibition of NADPH oxidase due to the increased hydrophobicity of the apocynin dimer over the parent compound. These studies corroborate with that reported by Potje (2017), in which the levels of nitric oxide, ROS, and calcium in aortic endothelial cells stimulated by diapocynin by apocynin were evaluated. The results presented by the author indicated that diapocynin showed a higher antioxidant capacity than apocynin, concerning the promotion of hypotensive effects without alteration of heart rate.…”
Section: Apocyninsupporting
confidence: 91%
“…The same author further justifies the increased inhibition of NADPH oxidase due to the increased hydrophobicity of the apocynin dimer over the parent compound. These studies corroborate with that reported by Potje (2017), in which the levels of nitric oxide, ROS, and calcium in aortic endothelial cells stimulated by diapocynin by apocynin were evaluated. The results presented by the author indicated that diapocynin showed a higher antioxidant capacity than apocynin, concerning the promotion of hypotensive effects without alteration of heart rate.…”
Section: Apocyninsupporting
confidence: 91%
“…Corroborant with these ndings, dimers as diferulic acid and diapocynin were also reported as better antioxidants compared to their monomer precursors. 11,28 It is worthy of note that MV is a methoxy-substituted catechol, a family of compound for which the potential therapeutic application is continuously increasing. The best example of this assertion is apocynin (acetovanillone).…”
Section: Synthesis and Redox Propertiesmentioning
confidence: 99%
“…7,10,[30][31][32] Homodimers of these methoxy-substituted catechols also have biological effects and, sometimes, superior to their precursors, as have been demonstrated to diapocynin, and divanillin. 10,11,33,34 Usually, the antioxidative efficacy of these dimers is increased.…”
Section: Synthesis and Redox Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is a great chance that divanillin can be as active as diapocynin regarding its biological activities. It's worth remembering that apocynin, an inhibitor of the NADPH oxidase enzymatic complex, has numerous pharmacological effects [9,10], and there is increasing evidence that diapocynin is also a promissory drug [1113]. …”
Section: Introductionmentioning
confidence: 99%